The land and people of Cambodia - Chandler, David P. (New York, NY : HarperCollinsPublishers, 1991)
Introduces the history, geography, people, culture, government, and economy of Cambodia.
Filmography: p. 201. Discography: p. 201.
Includes bibliographical references (p. 196-201) and index.
Keywords: Cambodia -- History; Kamboçya -- Tarih; Cambodia; Kamboçya